Child fostering and health nutritional outcomes of under-five: Evidence from Cameroon - Armand Mboutchouang Kountchou; Cédric Foyet Kamga; Cédrick Kalemasi Mosengo (African Governance and Development Institute (AGDI), 2023)
The objective of this article is to analyze the effect of child fostering on health nutritional outcomes of under-five children in host households in Cameroon. The data used comes from the recent Cameroon Demographic and Health Survey (DHS-V, 2018). Three anthropometric measures of health and nutritional status are retained: stunting, underweight and wasting. The estimation of a recursive bivariate probit model correcting the endogeneity bias of child fostering shows that fostering improves the health nutritional outcomes of children respectively by 1.14% for the risk of stunting, by 1.97 % for the risk of underweight and 1.28% for the risk of wasting. These results are mainly explained by a better investment in human capital by the parents of the host families. Moreover, robustness analyses show that the participation of women in the labor market in host households is an important transmission channel through which child fostering improves the nutritional health of children. This evidence reinforces the interest of women's empowerment policies to guarantee the improvement of the nutritional health of children, since these are two related sustainable development goals.
Keywords: I1; D1; 330; Child fostering; nutritional health; under-five children; recursive bivariate probit; Cameroon